Assessment of change of quality of life in hospitalized terminally ill cancer patients - Jasińska, Magdalena; Tracz, Michał; Kurczewska, Urszula; Orszulak-Michalak, Daria (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : Palliative care is the active comprehensive care of a terminally ill patient and his family. The quality of life of palliative patients is used to measure the effectiveness of treatment, as well as to show the most important aims in the patient’s care. The objective of the present study was to assess the change of quality of life of hospitalized terminally ill palliative oncological patients, using the newly developed EORTC Core Quality of Life Questionnaire (QLQ-C15-PAL). Material and methods : The study was performed in the Palliative Care Unit in the Hospital of Bonifratres Convent in Łódź. A group of hospitalized terminally ill palliative patients with lung, breast, colon or prostate cancer was analysed. Multi-item scales assessing physical and emotional functioning, single items of somatic symptoms and global quality of life estimated subjectively by patient were used. The trial was prospective and 121 questionnaires were finally included in the analysis. Results and conclusions : The overall quality of life was in correlation with the type of diagnosed carcinoma, giving the best scores in prostate cancer and the poorest ones in lung carcinoma. During the end of life care performed in the Palliative Care Unit the subjective quality of life (QOL) and emotional functioning of patients did not worsen, and in some patients the above parameters improved. Some reduction of numerous somatic symptoms was observed. The different activities contributing to palliative care resulted in some reduction of several somatic symptoms (e.g. constipation, insomnia) determining the discomfort severity. The important factors negatively determining the overall QOL were fatigue and pain, eliminated partially only in some patients. The effectiveness of palliative care relating to overall QOL or improvement of several symptoms did not differ significantly among patients with various types of tumour.